Ultrasonographic measurement of renal length and cortical thickness in clinically healthy Korean raccoon dogs - Jang, Moonsun; Kim, Myeongsu; Han, Jae-Ik; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2025)
IntroductionUltrasonographic assessment of renal parameters is a useful noninvasive tool for evaluating kidney health. Although reference values for renal size have been established in domestic species such as dogs and cats, corresponding data are unavailable for wild Korean raccoon dogs (Nyctereutes procyonoides koreensis), an endemic canid species in Korea.MethodsThis retrospective study analyzed abdominal ultrasonographic images from 36 clinically healthy wild Korean raccoon dogs. Measurements included renal length, renal cortical thickness (RCT), and aortic diameter, obtained using standardized imaging protocols. The ratios of renal length-to-aortic diameter (length/Ao) and RCT-to-aortic diameter (RCT/Ao) were calculated. Statistical analyses included paired and independent t-tests and Pearson correlation coefficients to assess differences and relationships among variables.ResultsThe mean renal length was 49.17 ± 3.53 mm for the left kidney, 47.53 ± 3.83 mm for the right kidney, and 48.36 ± 3.75 mm when both kidneys were pooled. The mean length/Ao ratios of the left and right kidneys were 10.53 ± 1.49 and 10.13 ± 1.53, respectively. The mean RCT for both kidneys was 4.81 ± 0.58 mm, and the mean RCT/Ao ratio was 1.03 ± 0.18. No significant sex-based differences were observed. Aortic diameter showed a positive correlation with body weight, whereas both length/Ao and RCT/Ao ratios were negatively correlated with body weight.ConclusionThis study provides the first ultrasonographic reference values for renal length, cortical thickness, and their corresponding aortic diameter ratios in wild Korean raccoon dogs. These findings offer foundational data for renal imaging assessment in this species and contribute to the development of species-specific reference standards in wildlife veterinary medicine.